Relevansi Sikap Wara’ Menuntut Ilmu Dalam Kitab Ta’lim Muta’alim Menurut Syaikh Az Zarnuji Dengan Sikap Peserta Didik Generasi Milenial - Marisa Hannum Harahap (Journal on Education, 2024)
This research aims to determine the relevance of the Sikaf Wara' Seeking Knowledge in the Book of Ta'lim Muta'alim According to Az Zarnuji with the Attitudes of Millennial Generation Students. Islamic education has an important role in shaping students' attitudes and behavior based on Islamic values. This research explores the relevance of the wara' attitude in studying as described by Az-Zarnuji in his book Ta'lim Muta'alim, with the attitudes of today's students. The wara' attitude which includes being careful in distinguishing between halal and haram is considered an important principle that must be applied in the learning process to gain useful knowledge and blessings. In this research the author used the method. The method used is descriptive analysis with a qualitative approach, studying classical texts and conducting a survey of current student attitudes. library research or (library research). Namely research that originates from the results of library data collection because the object of study is Sheikh Az-Zarnuji's thoughts about being wara' when studying in his work Ta'limul Muta'allim. Therefore, the data needed is textual data, namely books about students' attitudes in books and books. The data collection technique in this research is by digging up information from library sources, data sources that have been collected, both primary and secondary. The data analysis technique used in this research is content analysis. The research results show that there is still a gap in wara' attitudes among millennial generation students, and educational strategies are needed that integrate these traditional values ​​with contemporary educational contexts.